Study of Coping Strategies and Hardiness among Mothers of Children with Cancer and Typical Children in Hamedan City - Mina Ghasemi Rahmatabadi; Nasrolah Erfani (Iranian Journal of Educational Research)
Objective: The current investigation was undertaken with the objective of examining the coping mechanisms and psychological hardiness of mothers with children diagnosed with cancer in comparison to those with typically developing offspring. Methods: The methodological framework of this inquiry adhered to a descriptive, causal-comparative design, with the statistical population encompassing all mothers of pediatric oncology patients receiving treatment at Ekbatan Children's Hospital in Hamadan, alongside mothers of typically developing children within Hamadan during the year 2024. Employing the Cochran formula, a sample consisting of 100 mothers of children with cancer and 100 mothers of children without cancer was selected. The empirical data were subjected to analysis through the Coping Strategies Questionnaire and the Kobasa hardiness questionnaire, utilizing SPSS software and independent groups t-test for statistical evaluation. Results: The findings of the study elucidated that there exist significant disparities in coping strategies and psychological hardiness between mothers of children with cancer and those of normal children. Furthermore, the outcomes of the two sub-hypotheses of the study corroborated the presence of differences in both emotion-oriented and problem-oriented coping strategies as well as in the hardiness levels of mothers of children with cancer compared to those with normal children. Conclusions: In light of these findings, it was observed that emotion-oriented coping strategies are more prevalent among mothers of children with cancer, while problem-oriented strategies are more frequently employed by mothers of normal children. Additionally, psychological hardiness was found to be significantly greater in mothers of normal children compared to mothers of children with cancer.